Experimental Evaluation of Miniature Impedance Board for Loosening Monitoring of the Threaded Pipe Connection - Liang, Yabin; Chen, Yixuan; Zhang, Zuocai; Feng, Qian (Frontiers in Physics, 2021)
Electromechanical impedance (EMI)-based techniques have been widely used as a potential nondestructive evaluation (NDT) technique in the field of structural health monitoring (SHM), especially for the civil, mechanical, and aerospace engineering. However, one of the greatest challenges for this kind of technique is its impedance measurement hardware, which is usually expensive, bulky, and heavy, such as the professional impedance analyzer (WK6500B, Wayne Kerr), and thus seriously limited its practical application. In this paper, a small, lightweight and low power consumption SHM system combining with the low-cost miniature impedance board AD5933 was experimentally studied and investigated to validate its actual performance in the impedance measurement and structural damage identification. At first, the calibration and measurement procedure of AD5933 was detailly introduced by a simple impedance test for a free PZT patch, and its impedance calibration performance was also validated by comparing the signatures with ones measured by WK6500B. Then, in order to further validate its feasibility and effectiveness of the AD5933 in practical applications, a threaded pipe connection specimen was assembled in laboratory and then connected with AD5933 to acquire its impedance signatures under different loosening severities. The final results demonstrate that that measured impedance by the AD5933 presented a good consistence with the measurement by the WK6500B, and the evaluation board was successfully utilized for the loosening severities identification and quantitatively evaluation.